Unproductive electric losses in the traction power of DC supply system - Petrov, A. V.; Kostin, M. O. (Science and Transport Progress, 2010)
The research results specifying to the consumption of inactive (reactive by Fryze) power in a DC system of electric propulsion are stated in the article. It is shown that this consumption brings to considerable additional losses of electric energy in the system.